2022
DOI: 10.1161/jaha.121.023244
|View full text |Cite
|
Sign up to set email alerts
|

Association of Exposure to Abuse, Nurture, and Household Organization in Childhood With 4 Cardiovascular Disease Risks Factors Among Participants in the CARDIA Study

Abstract: Background We investigated associations of childhood abuse with 4 cardiovascular disease risk factors in adulthood, and whether exposure to nurturing and household organization in childhood mitigated these associations. Methods and Results The CARDIA (Coronary Artery Risk Development in Young Adults) study (baseline examination, 1985–1986) was used to examine associations of childhood exposures (measured retrospectively at the year 15 examination) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…One study with prospectively collected data from children with objectively determined (i.e., via court records) physical abuse and non-abused, case-matched counterparts showed that abused children had more risk factors for cardiovascular and cerebrovascular diseases in midlife (Widom et al, 2012). Similar findings have been shown in middle-aged adults who retrospectively reported childhood physical abuse (Aguayo et al, 2022; Carroll et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…One study with prospectively collected data from children with objectively determined (i.e., via court records) physical abuse and non-abused, case-matched counterparts showed that abused children had more risk factors for cardiovascular and cerebrovascular diseases in midlife (Widom et al, 2012). Similar findings have been shown in middle-aged adults who retrospectively reported childhood physical abuse (Aguayo et al, 2022; Carroll et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…Stroke may also link childhood adversity to poorer later-life cognitive function independent of educational attainment. Previous studies have linked childhood abuse and parental substance abuse to perturbed inflammatory responses (Carroll et al, 2013) and poor physical health outcomes (Aguayo et al, 2022). Chronic exposure to ACEs can become biologically embedded and lead to prolonged dysregulation in hormonal, inflammatory, and cardiovascular functions that impact health throughout the life course (Felitti, 2009; Miller et al, 2011; Su et al, 2015; Wade et al, 2019).…”
Section: Educational and Cerebrovascular Pathways Linking Aces To Cog...mentioning
confidence: 99%
“…Nearly a century after AHA began and half a century after commissioning of Cardiovascular Disease in the Young, the Children's Strategically Focused Research Network (SFRN) was established to apply state‐of‐the‐art basic, clinical, and population science strategies and train the next generation of pediatric cardiology scientists while still embodying Cardiovascular Disease in the Young's original focus on RHD, CHD, and preventive cardiology. The Children's SFRN directly and proudly builds on work done by the early pioneers in of pediatric cardiovascular science within AHA in the 1940s and 1950s.This article highlights the hypotheses, goals, accomplishments, challenges, and future directions of each center; provides an overview of collaboration efforts (Table 1 ) 1 , 2 , 3 , 4 and trainee accomplishments (Table 2 ) 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ; and summarizes how we can leverage the output of this SFRN to advance pediatric cardiovascular science.…”
mentioning
confidence: 99%
“…For example, prior studies show that adverse childhood environments are correlated with subclinical atherosclerosis, incident type 2 diabetes, hypertension, hyperlipidemia, and CVD and mortality in CARDIA and other cohorts. [20][21][22][23] Our study is among the first to modify the conceptual models of these collective studies to instead consider an outcome variable beyond metrics of disease or individual risk factors, and instead of a modifiable risk factor composite measure. This study further considers the protective exposure of caregiver warmth, beyond solely a risk exposure (adversity).…”
Section: Discussionmentioning
confidence: 99%